Testing The Applicability Of Scaling Law For Collisional Rate Coefficients - Sharma, M. K.; Chandra, S. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Вычисление столкновительных коэффициентов является сложной и трудной задачей. Когда эти данные недоступны, их значения могут быть оценены с использованием закона скейлинга (закон подобия/масштабная инвариантность). В некоторых исследованиях мы использовали закон подобия. Точные коэффициенты скорости столкновений для циклопропенилидена (c-C3H2) доступны в виде полного набора, что позволило анализировать возможность применения закона подобия. Рассмотрено по 50 вращательных уровней каждого из ортои паравидов c-C3H2 с энергиями до 91.53 см-1 и 87.21 см-1, соответственно. Сравнение результатов переноса излучения с использованием точных столкновительных коэффициентов с результатами, полученными с использованием закона подобия, показало, что результаты закона подобия являются качественными. Следовательно, для получения качественного поведения анализа использование закона подобия вполне разумно. Calculation of collisional rate coefficients is a challenging and difficult task. When these data are not available, their values may be estimated using a scaling law. In some investigations, we have utilized a scaling law. Accurate collisional rate coefficients for cyclopropenylidene (c-C3H2) as a complete set are available, and thus it may be appropriate occasion to test the applicability of that scaling law. We have considered 50 rotational levels of each of the ortho and para species of c-C3H2 having energies up to 91.53 cm-1 and 87.21 cm-1, respectively. We have compared the results of radiative transfer using accurate collisional rate coefficients with those obtained using the scaling law, and have found that the results of the scaling law are qualitative. Hence, for getting the qualitative behaviour of an analysis, the use of the scaling law is quite reasonable.
Keywords: Astrophysics